Targeting NRF2 Sensitizes Esophageal Adenocarcinoma Cells to Cisplatin through Induction of Ferroptosis and Apoptosis - Farah Ballout; Heng Lu; Zheng Chen; Tianling Hu; Lei Chen; Mary Kay Washington; Wael El-Rifai; Dunfa Peng (MDPI AG, 2022)
Esophageal adenocarcinoma (EAC), the predominant type of esophageal cancer in the United States, develops through Barrett's esophagus (BE)-dysplasia-carcinoma cascade. Gastroesophageal reflux disease, where acidic bile salts refluxate into the esophagus, is the main risk factor for the development of BE and its progression to EAC. The NFE2-related factor 2 (NRF2) is the master cellular antioxidant regulator. We detected high NRF2 protein levels in the EAC cell lines and primary tissues. Knockdown of NRF2 significantly enhanced acidic bile salt-induced oxidative stress, DNA damage, and inhibited EAC cell growth. Brusatol, an NRF2 inhibitor, significantly inhibited NRF2 transcriptional activity and downregulated the NRF2 target genes. We discovered that in addition to inducing apoptosis, Brusatol alone or in combination with cisplatin (CDDP) induced significant lipid peroxidation and ferroptosis, as evidenced by reduced xCT and GPX4 expression, two known ferroptosis markers. The combination of Brusatol and CDDP significantly inhibited EAC tumor xenograft growth in vivo and confirmed the in vitro data showing ferroptosis as an important mechanism in the tumors treated with Brusatol or Brusatol and CDDP combination. Our data support the role of NRF2 in protecting against stress-induced apoptosis and ferroptosis in EACs. Targeting NRF2 in combination with platinum therapy can be an effective strategy for eliminating cancer cells in EAC.